Chinese trade policy after (almost) ten years in the WTO: A post-crisis stocktake - Razeen Sally (European Centre for International Political Economy (ECIPE), 2011)
This paper interprets China's overall trade policy since its accession to the World Trade Organisation (WTO) almost a decade ago, and more recently in the wake of the global economic crisis. The first section briefly summarises policy trends leading up to WTO accession, as well as recent trade and foreign direct investment (FDI) patterns. The second section looks at China in the WTO: its record of implementing WTO commitments; its participation in the Doha Round; and in dispute settlement. The next section looks at China's trade-related reforms outside the WTO, especially unilateral measures and preferential trade agreements (PTAs). Section Four highlights challenges for China's trade policy: in the context of domestic reforms; in the WTO; in PTAs; in its key bilateral relationships; and in the context of global macroeconomic tensions. Section Five puts Chinese trade policy in a bigger domestic political-economy and geopolitical context. Section Six concludes. (...)
Keywords: 330; Außenwirtschaftspolitik; WTO-Mitgliedschaft; China